Pengadaan Tanah dalam Hutan Konservasi: Pengalaman Pembebasan Lahan Jalan Tol Balikpapan-Samarinda di Kawasan Taman Hutan Raya - Ilmadianti, Ilmadianti; Salim, M Nazir (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2024)
The existence of the land acquisition object for the construction of the Balikpapan-Samarinda toll road, which has the status of the Bukit Soeharto Grand Forest Park (Tahura) area, raises problems, namely being forced to change the spatial layout and provide compensation to the community because at the Tahura location there is land control by the community. This research aims to explain the mechanism for changing the designation of some conservation forest areas to Allocation for Other Uses (APL), look at the consequences of changing the designation of forest areas, and explain the process of compensation to communities that control APL in the